Rancangan Aplikasi Pengelolaan Data Gempa Bumi Stasiun Geofisika Nabire Berbasis Web - Oktavianus Frika Tampang; Ester Ayuk Pusvita (Jurnal Teknologi dan Informatika, 2025)
This exploration focuses on the development of a web- grounded operation designed to assist BMKG Nabire in managinng earthquake data more efficiently. The main thing is to streamline the process of recording and distributing earthquake information instantly and directly. Employing the Waterfall system as the development frame, the operation is erected to automatically present earthquake records and their corresponding chart visualizations. also, the system offers colorful data import options, including PDF, Excel, CSV, Word, and PNG formats. The final product is anticipated to significantly enhance the workflow of BMKG labor force in handling seismic information.